DBPs control in European drinking water treatment plants using chlorine dioxide: Two case studies - Ranieri, Ezio; Świetlik, Joanna (Journal of Environmental Engineering and Landscape Management, 2010)
The paper reports results of the experiments carried out at Fortore (Foggia, South Italy) and Mosina (Poznan, Poland) drinking water treatment plants aimed at DBPs control. Pilot scale GAC filters were installed in both plants in order to assess the efficacy of different kind of GAC for chlorites, NOM and THMs removal. Both pilot plants operated with and without chlorine dioxide pre‐disinfection. In Fortore plant, because of free chlorine was added in ClO2 pre‐disinfection solution, THMs formation was evaluated. Results showed an high efficacy of chlorites removal on GAC filters up to 5500 and 10000 bed volumes for mineral and vegetal GAC in Fortore and up to 11000 bed volumes in Mosina. A preliminary characterization of natural organic matter (NOM) dissolved in Fortore raw water was performed as well, in order to confirm its reactivity towards chlorine dioxide. The presence of small molecules (< 500 Da) in Fortore pre‐disinfected water, has resulted in THMs and carboxylic acids formation due a fast reaction with Cl2‐ClO2. GAC columns have shown percentages of removal ranging from 60 to 72% for THMs and ranging from 14.6 to 43% for TOC, so that adsorption represents an essential step for DBPs control.DBPs kontrolė Europos geriamojo vandens įrenginiuose ir vandens valymo efektyvumo tyrimai naudojant chloro dioksidąSantrauka. Straipsnyje pateikiami eksperimentų, darytų atliekant DBPs kontrolę Fortore (Foggia, Pietu Italija) ir Mosina (Poznan, Lenkija) geriamojo vandens ruošimo įrenginiuose, rezultatai. Eksperimentiniai skirtingos rūšies GAC filtrai, skirti chlorido, natūralių organinių medžiagų (NOM) ir THMs šalinimo efektyvumui nustatyti, buvo įrengti abiejuose vandens ruošimo įrenginiuose. Abu eksperimentiniai vandens ruošimo įrenginiai veikė atlikus pirminį dezinfekavimą chloro dioksidu ir dezinfekavimo neatlikus. Fortore vandens ruošimo įrenginiuose laisvąjį chlorą pridedant i ClO2 pirminės dezinfekcijos tirpalą, vertinta THMs susidarymas. Iš rezultatų buvo akivaizdu didelis chlorito sulaikymo GAC filtrais efektyvumas Fortore ir Mosina gyvenvietėse. Taip pat nustatytos preliminarios NOM, ištirpusių neapdorotame Fortore vandenyje, charakteristikos, taigi patvirtintas reaktyvumas su chloro dioksidu. Mažų molekulių (